Characterization of gp70 and Anti-gp70 Monoclonal Antibodies in Paracoccidioides brasiliensis Pathogenesis - De Mattos Grosso, Daniela; De Almeida, Sandro Rogério [UNESP]; Mariano, Mario; Lopes, Jose Daniel (American Society for Microbiology, 2003)
Paracoccidioidomycosis (PCM) is a systemic granulomatous mycosis whose agent is Paracoccidioides brasiliensis. In the culture supernatant, the fungus expresses glycoproteins of from 13 to 148 kDa. A cell surface glycoprotein of 43 kDa is the major antigenic component of P. brasiliensis. Another expressed glycoprotein, gp70, is recognized by 96% of sera from PCM patients and is able to induce lymphoproliferation. Since, little is known about this glycoprotein, we produced monoclonal antibodies (MAbs) against gp70 to isolate the molecule from total fungus extracts and to investigate its possible role in the pathogenesis of PCM. Using these MAbs, it was observed by confocal microscopy that gp70 is located mainly in the intracellular compartment of the fungus, although it was also detected in the culture supernatant. Based on observations showing that gp43 has a down-regulatory effect on mouse peritoneal macrophages, we tested the effects of gp70 on their phagocytic ability. Purified gp70 was able to inhibit the activity of macrophages through the mannose receptors and also through the Fc receptors; the latter effect was not observed with gp43. gp70 inhibits NO and H2O2 liberation by peritoneal macrophages in vitro, as does gp43. Results obtained with gp43 led us to hypothesize that gp70 could act as an escape mechanism for fungal establishment in primary infections. To corroborate this hypothesis, we analyzed the effect of passive immunization of mice during infection with P. brasiliensis using anti-gp70 MAbs. This treatment almost completely abolished granuloma formation in the lungs, suggesting that the protein facilitates fungal establishment and progression of lesions in primary infection.